Reduced graphene oxide (RGO)-SnOx (x=0,1,2) nanocomposite as high performance anode material for lithium-ion batteries - Wu, Yi-Zhu; Brahma, Sanjaya; Weng, Shao-Chieh; Chang, Chia-Chin; Huang, Jow-Lay (Journal of alloys and compounds, 2020)
Although, metal oxide-graphene nanocomposites and their applications in Li ion battery is a subject of intense investigation over the years, the synthesis of the composite that often needs high temperature processing along with expensive equipment are the major issues to overcome. We demonstrate a facile, low cost and room temperature synthesis of SnOX (x = 0,1,2) - reduced graphene oxide (RGO) nanocomposite where concurrent formation of SnO2, reduction of SnO2 to SnOx nanoparticles and graphene oxide to reduced graphene oxide takes place in one pot in-situ chemical reduction process. Concentration of the reducing agent (NaBH4, 0 mol–0.06 mol) is varied to examine the effect on the formation of the nanocomposite as well as their electrochemical performance. The RGO-SnOx nanocomposite prepared by using 0.04 mol of reducing agent reveal better Li storage performance, stable capacitance (833 mAh g−1 after 50 cycles, 767 mAh g−1 after 100 cycles, current rate = 100 mA g−1), and good rate capability (481 mAh g−1 at ∼1 A g−1). The lithium ion diffusion coefficient of RGO-SnOx (0.04 mol) nanocomposite is estimated as 2.4 × 10−10 m2s−1 that is one/two order higher than other RGO-SnOx nanocomposites which promotes the Li ion transport in the composite. The synthesis procedure has a strong potential to be one of the universal method for the preparation of a variety of composites by the suitable variant in the synthesis protocol. •Synthesis of SnOx/rGO (x = 0,1,2) nanocomposite at room temperature.•Room temperature chemical reduction procedure is used for the synthesis of the composite.•Enhanced capacity of 767 mAh g−1 @ 100 mA g−1 is achieved after 100 cycles.•The composite delivered significant rate capability (481 mAh g−1 at ∼1 A g−1).•Comprehensive investigation has been carried out.